Understanding growth and non-growth in entrepreneurial economies : analysis of startup industries and experimental winner generation in Finland, Israel and Silicon Valley - Sipola, Sakari (Acta Universitatis Ouluensis, ISSN 1796-2269, 2015)
Tiivistelmä suomeksi.
Keywords: startup-yritykset; kasvuyritykset; yritykset; kasvu